Fracture of aircraft titanium alloys under high-frequency loading - Alexander D. Nikitin; Pavel S. Shesterkin; Sergey S. Lopatin (SN Applied Sciences, 2023)
Abstract The paper is devoted to the problem of fatigue failure of two-phase titanium alloy VT3-1 under the action of high-frequency cyclic loading. Samples for the tests were made from the compressor disk of aviation engine D30-Ku installed on Tupolev Tu-154 planes. Repeated alternating loading was carried out by displacements of small amplitude at 20 kHz, coinciding with the first harmonic of longitudinal elastic vibrations of the sample. Analysis of specimen fracture surfaces shows predominant subsurface fracture. Analysis of areas of fatigue nucleation allows identifying elements of microstructure associated with crack nucleation. The results of the study can be used in the interpretation of fracture scenarios of structural elements in operation. Increasing the resource of products under such loads is possible through the use of damping layers or tapes, where possible.